'Indians are the Majority of the Prisoners'? Historical Variations in Incarceration Rates for Indigenous Women and Men in British Columbia. Issue 3 (8th September 2020) - INWOOD, KRIS; ROBERTS, EVAN
Abstract: Indigenous people have experienced relatively high incarceration rates in British Columbia, as elsewhere in North America, since the 1940s. Archival prison records, however, show that the incidence of Indigenous incarceration was lower than for other people before 1910. This evidence implies the crucial period for increasing incarceration of Indigenous peoples in British Columbias was from 1910 to 1940. The pattern for Indigenous women differed from that of men. Large numbers of Indigenous women were imprisoned in the 1870s and 1880s. The British Columbia Indigenous pattern has important similarities to the New Zealand Māori in the same era. Neither Indigenous experience is easily explained by group threat theory used to understand rising incarceration for African‐Americans in this period. Indigenous incarceration in settler states prior to the 1950s needs additional comparative research and theoretical understanding.